Microsoft Office Excel 2003 programming inside out - Frye, Curtis, 1968- (Inside out (Redmond, Wash.), 2004)
Take your Microsoft Office experience to the next level by programming custom business solutions with Excel 2003. This supremely organized reference and tutorial packs hundreds of timesaving answers, tips, and workarounds for advanced Excel users.